مظاههر الاتساق في النص القرآني : دراسة وصفية لغوية = Mazahir al-ittisaq fi al-nas al-Qur'ani : dirasah wasfiyah lughawiyah - Abdul Rahman, Lubna; Abd. Rahman, Akmal Khuzairy; Yeob, Shamsul Jamili (Department of Arabic Language and Literature, IIUM, 2011)
Cohesion is linguistic concept that has long been discussed by the traditionalscholars in their study of the Quranic text and its distinguished features. It is therefore the characteristics of the Holy Quran that further authenticate the relation between the Quranic verses through the various cohesive devices. The paper focuses on five of the cohesive features: Pronouns, deletion, replacement, repetition and linkage which are either from the category of cohesion by reference or by devices. The mechanisms of how these devices work in connecting the verses and ensuring the flow of thoughts and events thus ensuring the cohesiveness of the parts of ideas in the readership.